2018
DOI: 10.1002/bit.26827
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the genetic basis of fast l‐arabinose consumption on top of recombinant xylose‐fermenting Saccharomyces cerevisiae

Abstract: One major challenge in the bioconversion of lignocelluloses into ethanol is to develop Saccharomyces cerevisiae strains that can utilize all available sugars in biomass hydrolysates, especially the d-xylose and l-arabinose that cannot be fermented by the S. cerevisiae strain naturally. Here, we integrated an l-arabinose utilization cassette (AUC) into the genome of an efficient d-xylose fermenting industrial diploid S. cerevisiae strain CIBTS0735 to make strain CIBTS1972. After evolving on arabinose, CIBTS1974… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Further, several recombinant yeast studies that have reported using high density (20 OD) inoculum [25,26] did not include in the ethanol yields or productivities the material and time required to generate the inoculum. In many other ethanol-from-lignocellulosic studies, it is common to use high inoculum, supplementing the medium with yeast extract and peptone [29,32,51,52], corn steep liquor [35], or other nutrients [54]. It is not always clear if the inocula or these added carbon/nutrient sources are included in the total carbon balances when yields are reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, several recombinant yeast studies that have reported using high density (20 OD) inoculum [25,26] did not include in the ethanol yields or productivities the material and time required to generate the inoculum. In many other ethanol-from-lignocellulosic studies, it is common to use high inoculum, supplementing the medium with yeast extract and peptone [29,32,51,52], corn steep liquor [35], or other nutrients [54]. It is not always clear if the inocula or these added carbon/nutrient sources are included in the total carbon balances when yields are reported.…”
Section: Discussionmentioning
confidence: 99%
“…First, the yeast biomass production was accounted for in the conversion of glucose to ethanol. Conversely, most reported ethanol fermentations use yeast inoculums on the order of 10 to 50 g dcw/L (or 1.75 to 3.5 × 10 7 cell/mL) [18,30,32,[34][35][36]58,59]. In these high inoculum cases, it is not apparent that the yield from sugar to ethanol accounts for the sugar used to generate the biomass, which for the 10 g/L case would be at least 20 g/L of glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of L-arabinose into D-xylulose-5-phosphate is based on heterologous expression of bacterial genes encoding L-arabinose isomerase (AraA), L-ribulokinase (AraB), and L-ribulose-5-phosphate-4epimerase (AraD). Further improvements on alcoholic fermentation of these most abundant pentoses have been obtained through directed-evolution strategies aimed to accumulate spontaneous beneficial mutation [5][6][7]. A redox engineering study has revealed that deletion of S. cerevisiae genes encoding glycerol-3-phosphate dehydrogenase and expression of an acetylating acetaldehyde dehydrogenase from Escherichia coli (A-ALD) allow researchers to achieve conversion of inhibitory acetic acid to ethanol and to eliminate glycerol formation in anaerobic cultures of yeast [3].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Although S. cerevisiae cannot utilize xylose naturally (Ma and Liu, 2010;Wang et al, 2019), it can use xylulose, an isomer of xylose, to produce ethanol, making it attractive to introduce xylose metabolism pathways derived from other microorganisms to S. cerevisiae (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%